واقع الذكاء الإقتصادي ودوره في الميزة التنافسية في المؤسسات الإقتصادية - بن داني محمد, تبيب محمد (My University, 2022)
This study aims to understand the relationship between economic intelligence and the competitive advantage of Algiers Telecom Mostaganem, and as an attempt to know the role of economic intelligence in achieving a competitive advantage. In order to reach the answer to the problem posed: How can economic intelligence achieve a competitive advantage for Algeria Telecom Mostaganem, we used the descriptive analytical approach, where the study reached a set of results, which are the presence of positive and statistically significant correlations between economic intelligence and the elements of the dimensions of competitive advantage represented in (Cost, Quality, Excellence), as well as proving the validity of a correlation and significant relationship between economic intelligence and dimensions of competitive advantage.” Finally, we found a significant correlation between economic intelligence and dimensions of competitive advantage.
دراسة حالة مؤسسة إتصالات الجزائر وكالة مستغانم
Keywords: economic intelligence،competitive advantage،/economic information